Branding Wasuemba Village Tourism Potential through a Website-Based BUMDes Information System - Mahyudin Mahyudin; Muhammad Rizal Ardiansah Putra; Wa Nur Fida (Room of Civil Society Development, 2025)
This community service program aimed to enhance the competitiveness of tourism potential and local products in Wasuemba Village through an integrated digital branding strategy supported by a website-based Village-Owned Enterprise (BUMDes) information system. The partner, BUMDes Bantea Mainawa Lahonduru, faced limitations in product branding and the effective use of information technology for promotion. The program employed a participatory approach consisting of socialization, mentoring and digital marketing training, development and implementation of an official BUMDes website, and the installation of Starlink-based internet connectivity to support digital access. The results show improved capacity of BUMDes administrators in managing digital platforms and content, as well as increased readiness to utilize the website as a central information and promotion hub. The website strengthens the village’s digital identity, supports sustainable tourism promotion, improves transparency, and expands market reach. Overall, this program demonstrates that the integration of digital infrastructure and capacity building can accelerate digital transformation and support local economic development in rural and coastal communities.